EXPLOSION OF ANNULAR CHARGE ON DUSTY SURFASE - V. A. Levin; V. V. Markov; G. B. Sizykh (Научный вестник МГТУ ГА, 2017)
This problem is related to the safety problem in the area of forest fires. It is well known that is possible to extinguish a fire, for example, by means of a powerful air stream. Such flow arises from the explosive shock wave. To enhance the im- pact of the blast wave can be used an explosive charge of annular shape. The shock wave, produced by the explosion, in- creased during moves to the center and can serve as a means of transportation dust in the seat of the fire. In addition, emerging after the collapse of a converging shock wave strong updraft can raise dust on a greater height and facilitate fire extinguishing, precipitating dust over a large area. This updraft can be dangerous for aircraft that are in the sky above the fire. To determine the width and height of the danger zone performed the numerical simulation of the ring of the explosion and the subsequent movement of dust and gas mixtures. The gas is considered ideal and perfect. The explosion is modeled as an instantaneous increase in the specific internal energy in an annular zone on the value of the specific heat of explosives. The flow is consid- ered as two-dimensional, and axisymmetric. The axis of symmetry perpendicular to the Earth surface. This surface is considered to be absolutely rigid and is considered as the boundary of the computational domain. On this surface is exhibited the condition of no motion. For the numerical method S. K. Godunov is used a movable grid. One system of lines of this grid is moved in accordance with movement of the shock wave. Others lines of this grid are stationary. The calculations were per- formed for different values of the radii of the annular field and for different sizes of rectangular cross-sectional of the annular field. Numerical results show that a very strong flow is occurring near the axis of symmetry and the particles rise high above the surface. These calculations allow us to estimate the sizes of the zone of danger in specific situations.